Hybrid application of location service based on mobile signaling data analysis and base station positioning technology - Qing LI; Xuechun YAN; Sizhong CHEN (Dianxin kexue)
Location services based on mobile signaling data analysis and base station positioning services are two different user location services.One is the real-time positioning service; the other is the location service based on historical signaling data analysis,and they all have their own advantages and disadvantages.Some technical solutions that combined the base station real-time positioning with the open capability of mobile signaling data analysis based on historical trajectory and regional population statistics were presented,and the implementation of these methods were described in detail.A new idea for telecom operators to open and optimize their location capability based on network signaling was provided.